2019
DOI: 10.5897/ajfs2019.1805
|View full text |Cite
|
Sign up to set email alerts
|

Welfare effects of transportation cost and food price volatility in the context of globalization in Nigeria

Abstract: Globalization has enhanced the development of the transport sector and more importantly, the distribution of agricultural produce and food globally. However, not much is known about how this has impacted the welfare of the poor in Nigeria. Therefore, the study probed the persistence and asymmetry in food and transport price volatility; creating a dummy with the period before and after the adventure of significantly improved internet facility like 3G allowed the study to observe the significant effect of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The study revealed that significant number of the households were food insecure, thus calls for appropriate policy interventions (Anugwa and Ugwu, 2022). Other studies also revealed that food price inflation limits households food purchase (Egwuma et al, 2017), food quality, preference for different healthy foods, compromised good feeding habit (Ikuemonisan and Akinbola, 2019), and caused food insecurity. The impact of food inflation on food security and malnutrition have been documented (Headey and Ruel, 2022;Woldemichael et al, 2017;Lee et al, 2013;Arndt et al, 2012;Meerman and Aphane, 2012).…”
Section: Effects Of Energy Price Shock On Food and Nutrition Securitymentioning
confidence: 91%
“…The study revealed that significant number of the households were food insecure, thus calls for appropriate policy interventions (Anugwa and Ugwu, 2022). Other studies also revealed that food price inflation limits households food purchase (Egwuma et al, 2017), food quality, preference for different healthy foods, compromised good feeding habit (Ikuemonisan and Akinbola, 2019), and caused food insecurity. The impact of food inflation on food security and malnutrition have been documented (Headey and Ruel, 2022;Woldemichael et al, 2017;Lee et al, 2013;Arndt et al, 2012;Meerman and Aphane, 2012).…”
Section: Effects Of Energy Price Shock On Food and Nutrition Securitymentioning
confidence: 91%
“…The result obtained showed that fermentation greatly reduced the zinc content and value is slightly lower than 0.05 to 1.24 mg/100g reported by Owuno et al (2021) for gari fermented with maize residue. Findings show that 8-11 mg/day is recommended daily for adolescents and 12-19 mg/day for adults (Idris, 2011). In the body tissues zinc is needed for healthy cell division.…”
Section: Proximate Composition Of Cowpea Hull-enriched Garimentioning
confidence: 99%
“…Cassava was known for its wide ecological adaptability and could perform relatively well, although other crops may not be able to produce reasonable yield (Otekunrin and Sawicka 2019). Because of these characteristics, cassava can be a reliable food security for farming households in the tropics (Ikuemonisan and Akinbola 2019) and a livelihood for millions of farmers and traders worldwide (FAO 2018). In Nigeria, cassava is an integral part of the household diet.…”
Section: Introductionmentioning
confidence: 99%